ECADOC summer schools: quality assurance and enhancement - Katsarov, Johannes W. (Newsletter, 2017)
The European Doctoral Programme in Career Guidance and Counselling (ECADOC), financially supported by the European Commission under the Lifelong Learning Programme from 2013-2016, had two key objectives. The first objective was to formulate a joint research agenda, with the aim of inspiring cooperative trans-disciplinary research in our field in the future. The second objective was to organise a first series of annual summer schools, to support the emergence of a generation of early-stage researchers, who are dedicated to the practice of career guidance and counselling, international and trans-disciplinary cooperation. The sustainability of our efforts - building something to last - has always been at the heart of this project. Hence, questions of assuring quality and reaching excellence have guided us since we first came up with the idea of ECADOC.The purpose of this article is to share our concepts of quality assurance and enhancement for the summer schools of ECADOC, and to illustrate some of the central lessons, which we have learned over the past three years.